Visualisering av hovleden hos häst med magnetresonanstomografi - Pylkkänen, Maria (SLU/Dept. of Clinical Sciences (until 231231), 2013)
Lameness localized to the hoof is a common problem in horses. Magnetic resonance imaging (MRI) as a diagnostic tool is becoming more common and is well suited for examination of the distal limb and the hoof capsule. Today there are two different methods of MRI where in one the horse is under general anesthesia and in the other the horse is standing and only sedated. In this study we have compared the visualization of the distal interphalangeal joint using these two methods in two different groups of horses with unknown clinical problems referred to two different equine hospitals. The width of the joint structures including thickness of joint cartilage and joint fluid and also the width of the dorsal pouch of the distal interphalangeal joint were measured. The results showed that there was no significant difference between the width of the summarized joint structures, the thickness of the joint cartilage on the hoof bone or on the width of the joint fluid. The joint cartilage of the distal P2 was significantly thicker on the standing horse, which was an unexpected result. The dorsal pouch was wider on the standing horse, which you should be aware of when assessing MRI scans of the foot of standing horses. There are several sources of error to consider and it would be desirable with a larger study where clinically healthy horses were examined with MRI both standing sedated as well as under general anesthesia in a short interval of time.